1991
DOI: 10.1073/pnas.88.23.10951
|View full text |Cite
|
Sign up to set email alerts
|

T cells expressing the V beta 1 T-cell receptor are required for IgA production in the chicken.

Abstract: While afi T cells in mammals may express one of many variable (V) gene families in the 13 had greater than normal numbers of Vp2' T cells and appeared as healthy as thymectomized and untreated controls. While production of IgM and IgG antibodies was unimpaired, IgA antibody production was severely compromised in the Vpldepleted birds. The levels of secretory IgA in bile and lung lavage fluid were reduced 1000-to 10,000-fold and secretory IgA antibodies were not produced in response to mucosal immunization. B-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 23 publications
5
30
0
Order By: Relevance
“…The recent observation that TCR2 cells that express the V,91 gene segment were found to be required for IgA production (26) further suggests that the chicken model system may provide insight into the role of distinct and evolutionarily conserved T-cell subsets.…”
Section: Resultsmentioning
confidence: 99%
“…The recent observation that TCR2 cells that express the V,91 gene segment were found to be required for IgA production (26) further suggests that the chicken model system may provide insight into the role of distinct and evolutionarily conserved T-cell subsets.…”
Section: Resultsmentioning
confidence: 99%
“…The different sub-populations of the αβ T cells, such as those differentiated by the V region of the chain, Vβ1 + (TCR2) or Vβ2 + (TCR3) [75], or by the accessory receptor molecules CD4 + or CD8 + [92], have distinct functional activities [3,26]. The amount and proportion of the T cell sub-populations in blood and in peripheral tissues have been correlated with differences in disease susceptibility [135,139].…”
Section: T Cell Receptorsmentioning
confidence: 99%
“…Using haemolytic plaque assays Lawrence et al [38] demonstrated that these cells actively secret IgA. Since IgA can be obtained by lung lavage at readily detectable concentrations [13] it seems likely that IgA + cells in the tissue are the prime source of secretory IgA in the chicken lung. However, it is still unknown if the poly-Ig receptor is expressed on the lung epithelium and distribution of IgA secreted in the upper respiratory [2,57] tract into the lung can not be excluded so far.…”
Section: Secretory Immunoglobulins -The Iga Systemmentioning
confidence: 99%